Preparation and characterization of timed drug delivery system of sumatriptan using natural polymers - Al-anbagi, Mina Shihab; A. Rajab, Nawal; I.Khalil, Yehia (Iraqi Journal of Pharmaceutical Sciences, 2018)
Pulsatile drug delivery systems are time-controlled dosage forms which are designed to release the active pharmaceutical ingredient after a predetermined lag time to synchronize the disease circadian rhythm. A migraine shows circadian rhythm with a marked increase in attacks between 6 a.m. and 8 a.m. Sumatriptan is a selective agonist at serotonin (5-Hydroxy tryptamine1 (5-HT1))receptors, is an effective treatment for acute migraine attacks. The aim of this work is to prepare time-controlled press-coated tablet with a lag time of 5.45 hrs. Six formulas of fast dissolving core tablets and three formulas of press-coated tablets were prepared by using direct compression method using different variables to prepare core tablets which include: different types and concentrations of superdisintegrants While different concentrations of natural and synthetic polymers were utilized in the preparation of press-coated tablets. The obtained results showed that formula F4 of core tablet, which contained 25 mg of sumatriptan, 5% w/w sodium starch glycolate and avicel PH 102 as the diluent, was the selected formula that gave the fastest and complete release of sumatriptan. Also, formula C3 of the press-coated tablet, which contained pectin: EC100 mpa.s: HPMCK15M in concentration30mg: 10mg:160mg respectively, was selected as the best coating layer since it gave 5.45 hours lag time.